Study of the Effect of Fresh Green Asparagus officinalis L. Stems Extract and Metformin Drug on Induced Polycystic Ovary Syndrome (PCOS) in Female Albino Rats - Shaheen, Alaa Ali; Hussain, Kiaser Abdulsajjad M.; Al-Safy, Alaa Hussein (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
During this research, Polycystic Ovary Syndrome (PCOS) was studied and the effect of Metformin Drug and an extract of fresh Asparagus officinalis L. stems on it was studied. The study involved 20 adult female albino rats divided into four groups, each containing five female rats. The first group received a physiological saline solution, while the second group was induced with Polycystic Ovary Syndrome (PCOS) by being dosed with Letrozole. The third group, after the induction of PCOS, was treated with Metformin, and the fourth group was dosed with Fresh Asparagus officinalis L. stems extract. The study focused on hormonal and Histological changes. The results showed that the group of rats with PCOS induced by Letrozole had a significant decrease in the levels of Progesterone (Prog.) and Oestradiol (E2) hormones, and a significant increase in Testosterone (Testo.) compared to the control group. Dosing rats with Fresh Asparagus officinalis L. stems extract led to a significant decrease in (E2) hormone level and a significant increase in Progesterone (Prog.) hormone level compared with the control group. Dosing rats with Metformin led to a significant decrease in (E2) hormone level and a significant increase in Progesterone (Prog.) and Testosterone (Testo.) hormone levels compared to the control group. The results also indicated significant changes in hormone levels between Treatment groups and PCOS induction group. The histological study revealed changes in the shape of the ovary, the appearance of cystic structures, congestion of blood vessels, and increased ovarian cellularity. Metformin showed fewer Histological changes, while Asparagus officinalis L. stems extract had a therapeutic effect with moderate severity, leading to the disappearance of cystic vesicles and the appearance of corpus luteum and primary vesicles. In conclusion, we conclude that both the therapeutic agents Metformin and the extract of Fresh Asparagus officinalis L. stems showed a therapeutic effect on Polycystic Ovary Syndrome, as Metformin drug showed a treatment for this Syndrome, but it requires a long period to show this result, meaning we need more than 28 days, which is the duration of the study, but Asparagus officinalis L. stems extract had Faster healing effect within just 28 days. Fresh Green, tender Asparagus officinalis L. stems is one of the significant medicinal plants that is used to treat or prevent polycystic ovarian syndrome. Research has shown that it is an effective treatment for the condition. Future researchers studying polycystic ovarian syndrome will find this article useful.